Analisis Faktor Faktor Yang Mempengaruhi Kinerja Bongkar Muat Dengan Fishbone Analysis di Terminal Mustika Alam Lestari - Leki, Michael Julianto; Ramadhan, Wicaksono Rezeki (Institut Transportasi dan Logistik Trisakti, 2024)
PT Mustika Alam Lestari is one of the companies engaged in port services in Indonesia. The company focuses on providing loading and unloading services at port terminals, as well as managing other supporting facilities related to port activities. PT Mustika Alam Lestari (MAL) was selected as a partner of PT Multi Terminal Indonesia (MTI) in the operation of Berths and Stacking Fields 214 and 300 as a “multipurpose” terminal at Tanjung Priok port. This research uses descriptive analysis method. Based on the results of the Fishbone analysis, several main factors that hinder the loading and unloading process at Terminal Mustika Alam Lestari were identified, namely the Man, Method, Machine, and Enviroment factors. Based on the identification of obstacles above, several recommendations can be taken to minimize inhibiting factors and improve loading and unloading performance: HR Training and Development, Process and Method Optimization, Equipment Maintenance and Modernization, and Handling External Conditions.